Evaluation of a Video Decision Aid to Reduce Decisional Conflict in Physician Orders for Life-Sustaining Treatment (POLST) Decision-Making. Issue 4 (October 2020) - Gallegos, Jarred V.; Edelstein, Barry; Moss, Alvin H.
Background/Objectives: Physician Orders for Life-Sustaining Treatment (POLST) is recommended as a preferred practice for advance care planning with seriously ill patients. Decision aids can assist patients in advance care planning, but there are limited studies on their use for POLST decisions. We hypothesized that after viewing a POLST video, decision aid participants would demonstrate increased knowledge and satisfaction and decreased decisional conflict. Design: Pre-and postintervention with no control group. Setting/Participants: Fifty community-dwelling adults aged 65 and older asked to complete a POLST based on a hypothetical condition. Interventions: Video decision aid for Sections A and B of the POLST form. Measurements: Pre- and postintervention participant knowledge, decisional satisfaction, decisional conflict, and acceptability of video decision aid. Results: Use of the video decision aid increased knowledge scores from 11.24 ± 2.77 to 14.32 ± 2.89, P < .001, improved decisional satisfaction 10.14 ± 3.73 to 8.70 ± 3.00, P = .001, and decreased decisional conflict 12 ± 9.42 to 8.15 ± 9.13, P < .001. All participants reported that they were comfortable using the video decision aid, that they would recommend it to others, and that it clarified POLST decisions. Conclusions: Participants endorsed the use of a POLST video decision aid, which increased their knowledge of POLST form options and satisfaction with their decisions, and decreased their decisional conflict in POLST completion. This pilot study provides preliminary support for the use of video decision aids for POLST decision-making. Future research should evaluate a decision aid for the entire POLST form and identify patient preferences for implementing POLST decision aids into clinical practice.